A study of compressibility and compactibility of directly compressible tableting materials containing tramadol hydrochloride - Mužíková Jitka; Kubíčková Alena (Acta Pharmaceutica)
The paper evaluates and compares the compressibility and compactibility of directly compressible tableting materials for the preparation of hydrophilic gel matrix tablets containing tramadol hydrochloride and the coprocessed dry binders Prosolv® SMCC 90 and Disintequik™ MCC 25. The selected types of hypromellose are Methocel™ Premium K4M and Methocel™ Premium K100M in 30 and 50 % concentrations, the lubricant being magnesium stearate in a 1 % concentration. Compressibility is evaluated by means of the energy profile of compression process and compactibility by the tensile strength of tablets. The values of total energy of compression and plasticity were higher in the tableting materials containing Prosolv® SMCC 90 than in those containing Disintequik™ MCC 25. Tramadol slightly decreased the values of total energy of compression and plasticity. Tableting materials containing Prosolv® SMCC 90 yielded stronger tablets. Tramadol decreased the strength of tablets from both coprocessed dry binders.